Anthropometric Measurements in Different Ethnic groups of Nepalese New Borns - Malla, K; Mall, T; Rao, S; Gauchan, E; Basnet, S; Koirala, DP (Journal of Nepal Paediatric Society, 2012)
Introduction: There is a wide variation in normal birth weight, length and head circumference of newborns. The standards formulated by Western workers may not be very reliable to this part of world because of wide variations in normal range of length, weight and head circumference in different ethnic groups. This study aims to determine the anthropometric values – birth weight, length and head circumference in Term and Preterm newborns of different ethnic groups in this region of the country and to see if this can be used as a standard for taking the anthropometric measurements. Materials and Methods: A prospective study of 600 newborns born in Manipal Teaching Hospital, Pokhara from July 2009–June 2010. A detailed anthropometric measurement (weight, length, and head circumference) of all newborns was taken on 3rd day of life. Results: Six major Ethnic groups were noted Brahmin, Gurung, Dalit, Chettri, Magar and Newar. There were 54 % males and 46% females among which 18.16% were preterms, 20.66% small for gestation age, 81.50% term and 0.33% posterm. The mean weight, length and head circumference of term babies were 2.817±0.61 gms, 47.68±2.48 cm, 33.56±2.02 cm and for preterm babies it was 2.215± 0.41 gms, 46.36±2.39 cm, 32.23±2.03 cm respectively. There were 25% low birth weight (n=151, highest number in Brahmins-27%), 74.16% normal weight (n=445) and 0.66% over weight (n=4, all were gurungs) babies. In Term newborns weight, length and head circumference was noted to be highest in Gurungs (3.3004gms, 49.35cm, 34.72cm) and was statistically significant (p<0.000). Weight and length of Brahmins was lowest (2.578 gms, 45.49cm) and head circumference was lowest in Dalits (30.88cm, statistically significant<0.000). In case of preterms highest weight and length was seen in Magars (2.387gms, 47.90cm) but head circumference was highest in Gurungs (34.18cm) whereas weight was lowest in chettri (2.1609gms), length in Brahmin (44.61cm) and OFC in Dalits (29.92cm). These parameters were directly proportion with gestation age and was statistically significant (p<0.000). Conclusion: The present study highlights the mean weight, length and head circumference of term and preterm newborns in different ethnic groups and gestation age. These parameters were directly proportion to gestation age but were variable in different Ethnic groups. Therefore a study in larger population could give us a different standard for anthropometric measurements in Nepalese newborns. Key words: Anthropometry Measurements; Newborn; Nepal DOI: http://dx.doi.org/10.3126/jnps.v32i1.4880 J. Nepal Paediatr. Soc. Vol.32(1) 2012 1-8